2022
DOI: 10.3390/ijerph19063291
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with an Outbreak of COVID-19 in Oilfield Workers, Kazakhstan, 2020

Abstract: From March to May 2020, 1306 oilfield workers in Kazakhstan tested positive for SARS-CoV-2. We conducted a case-control study to assess factors associated with SARS-CoV-2 transmission. The cases were PCR-positive for SARS-CoV-2 during June–September 2020. Controls lived at the same camp and were randomly selected from the workers who were PCR-negative for SARS-CoV-2. Data was collected telephonically by interviewing the oil workers. The study had 296 cases and 536 controls with 627 (75%) men, and 527 (63%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Our seroprevalence study for the first time documents an extremely high rate of SARS-CoV-2 exposure in Karaganda, Kazakhstan. Although pilot in nature, these findings are consistent with high SARS-CoV-2 seroprevalence in other regions of Kazakhstan [ 19 , 20 , 33 ], corroborating an overall underascertainment of COVID-19 rates across the country. While narrowing the gaps in country-wide infection surveillance necessitates addressing systemic issues related to governance and healthcare delivery and improving vital registration systems, we hope that our findings can inform the regional pandemic response to facilitate a more effective and equitable distribution of resources, such as vaccines.…”
Section: Discussionsupporting
confidence: 75%
“…Our seroprevalence study for the first time documents an extremely high rate of SARS-CoV-2 exposure in Karaganda, Kazakhstan. Although pilot in nature, these findings are consistent with high SARS-CoV-2 seroprevalence in other regions of Kazakhstan [ 19 , 20 , 33 ], corroborating an overall underascertainment of COVID-19 rates across the country. While narrowing the gaps in country-wide infection surveillance necessitates addressing systemic issues related to governance and healthcare delivery and improving vital registration systems, we hope that our findings can inform the regional pandemic response to facilitate a more effective and equitable distribution of resources, such as vaccines.…”
Section: Discussionsupporting
confidence: 75%
“…For a detailed description of the number of references at each stage, see the Prisma flowchart in figure 1. Overall, the 19 studies included here provide evidence for the effectiveness (or ineffectiveness) of the following NPIs: ventilation (n = 12) [10][11][12][13][14][15][16][17][18][19][20][21]; air filtration/air cleaning devices (n = 4) [17,[26][27][28]; surface disinfection (n = 5) [20][21][22][23][24]; room occupancy (n = 6) [11,12,16,[24][25][26]; and screens/barriers (n = 1) [17]. No evidence was found on the use of CO 2 monitoring or one-way systems in reducing transmission.…”
Section: Resultsmentioning
confidence: 99%
“…No evidence was found on the use of monitoring or one-way systems in reducing transmission. These 19 studies covered a range of settings: healthcare facilities ( 6 ) [ 18 , 20 , 22 24 ]; residential ( n =3) [ 10 , 11 , 21 ]; meat-processing plants ( 2 ) [ 12 , 14 ]; school classrooms ( 2 ) [ 16 , 17 ]; an overnight camp ( 1 ) [ 25 ]; a bus ( 1 ) [ 13 ]; a restaurant ( 1 ) [ 26 ]; and an oilfield ( 1 ) [ 15 ]. Two studies were laboratory studies using animal models ( 2 ) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the analysis of literature data of both foreign and domestic authors made it possible to reveal that in order to assess the health of the working population as a whole, it is necessary to study comprehensively from the standpoint of occupational health and safety. A review of special scientific literature showed that the issues of organising the occupational health and safety service have not been studied, including the insufficiently developed monitoring system for the quality of professional activity, health and life of men employed in the main industries in the Republic of Kazakhstan (Kraus et al 2019, Matsuzaki et al 2020, Ballin et al 2020, Rohwer et al, 2022Nurbek et al, 2022;Nabirova et al, 2022;Durdyev et al, 2022).…”
Section: Introductionmentioning
confidence: 99%